The new species Daptonema pumilus sp. nov. (Nematoda: Monhysterida) in Vietnam - Thanh, Nguyen Vu; Hoang, Lai Phu; V. G., Gagarin (Academia Journal of Biology, 2014)
During 2003 year, the faunal free-living aquatic nematodes of the Cam estuary, Haiphong city and the Thivai river, Cangio mangrove, Hochiminh city had been investigated. Below, the description of one new nematode species to science Daptonema pumilus sp. nov. (Monhysterida) is given. Female: The new nematode species is a small and slender worm. Cuticle thin, transverse striation shallow, hardly visible. Somatic setae and crystalloid bodies absent. Stoma funnel-shaped, not cuticularized. Amphid fovea circular, 3.0-3.5 mm in diameter, its anterior margin situated at 1.4-1.6 labial region width from anterior body end. Oesophagus slender and muscular, swollen proximally. Cardia triangular, projecting into intestinal lumen. Rectum slightly shorter than anal body diameter. Reproductive system mono-prodelphic, ovary comparatively short, situated on the left side of intestine. Oogonia arranged in one or two rows. Oviduct short and inconspicuous. Vagina oblique, shorter than corresponding body diameter. Vulva situated on the posterior part to middle part of body. Posterior uterus sack absent. Tail long, gradually narrowing, usually curved dorsally. Two terminal setae 1.0-2.0 mm long on the tail terminal. Three caudal glands arranged in tandem, spinneret oblique. Male: Similar to female in general morphology, but somewhat shorter. Reproductive system mono-orchid. Spicules length as long as cloacal body diameter. Gubernaculum with dorsal appendix. Tail slender, gradually narrowing and curved dorsally; caudal glands three, tandem, spinneret conspicuous. This new species closes to Daptonema nanus, Lorenzen, 1971, but differs in having more front location of amphidial fovea, more back location of vulva (in D. nanus V = 58% vs V = 60.7-68.7% in D. pumilus) and presence of terminal setae at the tail (in D. nanus without terminal setae).